Anomali dalam Pemilihan Kepala Desa (Studi Kasus di Desa Kamal Kecamatan Pemulutan Barat Kabupaten Ogan Ilir) - Adellah; Azhar, Azhar; Alya Syafitri Lubis (Universitas Medan Area, 2024)
This reserach aims to find out the anomalous phenomenon in the election of village heads in Kamal village, West Pemulutan District, Ogan Ilir Regency. The problem focuses on anomalies in the election of village heads in Kamal village, West Pemulutan District, Ogan Ilir Regency. In order to approach this problem, social action theory by Max Weber is used as a reference because this theory is able to analyze actions such as what are the driving factors for anomalies in village head elections. Data was collected through documentation and interviews and analyzed qualitatively. This study concludes that the anomaly in the election of village heads in Kamal village, West Pemulutan District, Ogan Ilir Regency, is due to several social actions. The first is instrumental rational action, in the form of strategies used by each candidate for village head, such as conducting outreach to the community and putting up banners. Second, value-oriented rational actions, such as creating a vision and mission. Third, traditional actions in the form of identity politics. Fourth, namely affective actions, such as issues that develop in village community